Metaphors in Adhitia Sofyan’s Songs - Meidia Rea Smithiana; Sharifah Hanidar (Universitas Gadjah Mada, 2018)
This research examines the metaphors used by Adhitia Sofyan in his songs. The data used in this research were Adhitia Sofyan’s song lyrics taken from four different albums: Quiet Down (2009), Forget Your Plans (2010), How to Stop Time (2014), and Silver Painted Radiance (2016). The data were analyzed using the theory of conceptual metaphor proposed by Lakoff and Johnson (1980). The results show that the chosen song lyrics contain three kinds of metaphors: structural, orientational, and ontological metaphors. In addition, the messages Adhitia Sofyan wants to convey by using the metaphors are mostly about love towards a sweetheart, an ex-girlfriend, a mother, and God. The metaphors in the songs are also used to express feelings such as loneliness, regrets, hope, and despair.